The life and work of Stefan Pankovych, the Bishop of the Greek Catholic Eparchy of Mukachevo - Molnár Ferenc; Молнар Федір; Molnar Fedir (My University, 2021)
Abstract. When Bishop Stefan Pankovych (1866–1874), who succeeded Vasyl Popovych (died in 1864) was inaugurated, he was almost unknown to the Rusin clergy of the Greek Catholic Eparchy of Mukachevo. The new bishop maintained good relations with members of the Hungarian political elite and actively supported the policy of the Hungarian government. This was manifested on several levels. He promoted to high ecclesiastical positions those who did not support Adolf Dobriansky, a Russophile considered the most significant Rusin leader. Following the Austro-Hungarian Compromise of 1867, Rusin leaders had the opportunity to hold various offices, mainly with the trust of the Hungarian government and the Bishop of Mukachevo. In 1871, Bishop Stefan Pankovych and his followers removed Adolf Dobriansky and Ivan Rakovsky from the leadership in St. Basil the Great Society, which led to a gradual decline of the Russophile trend in the Rusin movement. The Great Russian camp supporters also confronted Stefan Pankovych because of the attempt to introduce the Gregorian calendar and the Latin alphabet in the Mukachevo Diocese. Even more moderate clergy were divided on such issues, because these concepts were important for Rusin identity. However, Stefan Pankovich’s unexpected death on August 29, 1874, temporarily froze debates in the Rusin movement.
Keywords: Stefan Pankovych; Greek Catholic Diocese of Mukachevo; Rusins; Russophiles; Adolf Dobriansky; Uzhhorod